207 IMPLEMENTATION OF A FRAILTY CARE BUNDLE (FCB) IN ACUTE AND REHABILITATION SETTINGS. (18th November 2021) - Naughton, C; Cummins, H; Foubert, M; Barry, F; Wills, T; McCullagh, R; Ahern, E
Abstract: Background: During hospitalisation older adults are at greater risk of hospital associated decline (HAD), attributed to hospital processes that fail to prioritise fundamental care related to mobility, nutrition and cognitive health. The study aims to enable the nursing and multidisciplinary team to prioritise early mobilisation, optimise nutrition and cognitive engagement in patients aged 60 years and older. Methods: Four wards were recruited, two orthopaedic trauma and two orthopaedic rehabilitation. Following situational analysis on each ward, we used behaviour change theory COM-B (capability, opportunity motivation) to align the intervention components to barriers. These included inter-professional communication (mobility board with patient goals, nurse & physiotherapy huddles, daily mobility record); staff knowledge (education, coaching, posters); nutrition opportunities (assisted mealtimes, MUST tool, enhanced snack rounds) and cognition (patient information leaflet, distraction activity resources). Data collection included observational audits of mobility measuring: % mean time walking, % patients sitting out of bed, % patients walked at last once, and nutrition: % of meals half or less eaten at baseline and 12-week follow-up. Each ward was observed from 8am to 5pm. Results: In total mobility audit data was collected on 124 patients (pre =63, post 61), mean age 78 years (SD13.8) and 63% female. Mean data across the four wards are presented. There were small positive changes in two mobility indicators: patients sitting out of bed (pre 69% vs post 76%); % patients walked at least once (pre 53% vs post 62%); there was no change in mean % time spent walking (pre 9% vs post 8%). Nutrition indicator: % meals <half eaten (pre 57.6% vs post 53%). Conclusion: The FCB showed some promising trends in prioritising mobilisation and nutrition. Implementation relies on ward manager leadership, nursing team cohesion, and active role modelling from the MDT. Sustainability is likely to require ongoing facilitation resource.